Green roof on the ventilation and pollutant dispersion in urban street canyons under unstable thermal stratification: Aiding and opposing effects. (December 2021) - Zhang, Wei-Chen; Luo, Xiang-Yu; Peng, Xin-Ru; Liu, Run-Zhe; Jing, Yi; Zhao, Fu-Yun
Highlights: Green roof influenced on the outdoor thermal buoyancy flow distributions in a wide range of H/W. Aiding and opposing effects were observed as wind and thermal buoyancy simultaneously acted. A "free air flow region" arose when the leeward green roof deployment was adopted. Lateral deployment of green roof system performed better than that of rooftop deployment. Rational design of the green roof system could enhance its cooling capacity. Abstract: The "thermal effect" of the green roof system on the pollutant dilution process would be analyzed in this research. Different arrangement schemes (on the rooftop, windward side and leeward side) of the green roof system would alter the thermal buoyancy distribution in the street canyon, thus change the overall flow field and pollutant dilution condition Computational Fluid Dynamics (CFD) technique along with the Renormalization Group (RNG) k-ε turbulence model has been adopted for the simulation work. Cases without the green roof system are assumed to be uniformly heated and are prepared for benchmark comparisons. Six aspect ratios ( H/W ) and ten ranks of unstable thermal stratifications ( Rb ) are selected to consider the influence of street canyon morphology and thermal buoyancy. Results demonstrate that the lateral deployment of green roof system performs better than the rooftop deployment and the situations without green roof system. In the windward cooling cases, a single vortex is formed in the canyon center and dramatically reduces the pollutant retention time τ when H/W > 1, while in the leeward cooling cases, a "free airflow" region is formed in all the tested aspect ratios expect for H/W = 0.5. The rooftop deployment scheme has negative effects, not just decaying ventilation performance, but also delaying pollutant dispersion period. Present research could benefit the rational design of the green roof system in the urban building clusters, and further enhance its cooling capacity for the built energy conservation.